Municipalização da saúde no Brasil: diferenças regionais, poder do voto e estratégias de governo - Arretche, Marta [UNESP]; Marques, Eduardo (Associação Brasileira de Saúde Coletiva (ABRASCO), 2002)
Este artigo examina a extensão e os determinantes do processo de municipalização da política de saúde no Brasil, com base na análise estatística de dados para 1.643 municípios localizados em diferentes regiões brasileiras. Inicialmente, analisa o alcance de duas dimensões do projeto de municipalização da saúde: a oferta municipal de serviços de atenção básica e a municipalização da gestão da rede hospitalar local. em seguida, discute o impacto de distintas variáveis na decisão municipal em favor da municipalização: porte e localização do município, suas capacidades fiscais, as preferências do eleitorado local, a competição eleitoral, o contexto local para a tomada de decisão, bem como o impacto local da estratégia federal de descentralização.

This article examines the extension and the determinants of the municipalization of health public policies in Brazil, using the results of a statistical analysis of data from 1,643 municipalities located in different Brazilian regions. We start by analyzing the importance of two dimensions of the process of decentralization of health public policies in recent Brazil: the municipal offer of basic health care services, and the municipalization of the regulatory power over local hospital facilities. Then, we discuss the impact of several variables on the increase of the municipal role in health public policies: size and location of the municipality, its financial capacity, the political preferences of the local constituencies, the level of electoral competition and the political context of the local decision making process, as well as the impact of the federal strategies of decentralization on local policies.
The municipalization of health care policies in Brazil: regional differences, the voting power and government strategies
Keywords: Política de saúde; Municipalização; Condições locais; Health policy; Municipalization; Local conditions